Evaluation of a Pharmacist-Based Intervention to Reduce Readmissions in Geriatric High-Utilizer Patients: A Pilot Study - Sara Turbow; Kruti Shah; Katherine Penziner; Michael Knauss (University of Minnesota Libraries Publishing, 2019)
Purpose: The goal of this study was to determine if a pharmacist-led intervention to improve medication safety at hospital discharge reduced the number of hospital readmissions among geriatric high-utilizer patients. This study is the first to test a pharmacist-based intervention in a high-utilizer population. Methods: This was a quasi-experimental pilot study done at a safety-net hospital in the southeastern US. Fifty-seven patients 65 years old and older who were in the 95th percentile for number of hospital admissions in a year were included. On the day of discharge, one of the study pharmacists reviewed the discharge medication list and calculated the Medication Appropriateness Index (MAI) for each medication and reviewed for Beers Criteria. Any medication identified as potentially high-risk or inappropriate was flagged by the pharmacist and discussed with the team. The primary outcome was the number of admissions in the year following the intervention in the intervention group versus the control group. Results: There were no statistically significant differences in the number of admissions, the MAI scores, or the number of medications meeting Beers Criteria between the two groups. Conclusion: Although this study did not demonstrate a decrease in hospital admissions, it shows that pharmacist review of medications at discharge can identify potentially unnecessary medications that could lead to confusion or adverse events. Further research is necessary to identify interventions to prevent readmissions in this high-risk population.   Article Type: Original Research